A dataset of dynamical social map in ancient China: 618−1644 - Xiong-Fei Jiang; Ling Bai; Na Zhao; Long Xiong (Data in Brief, 2023)
The data set of this article is related to the paper “Dynamical structure of social map in ancient China” (2022)[1]. This article demonstrates the data of social relations between cities in ancient China, ranging from 618 AD to 1644 AD. The raw data of social associations between elites used to build social maps are extracted from the China Biographical Database. The raw data contain 14,610 elites and 29,673 social associations, which cover 366 cities. The dataset of this article is relevant both for social and natural scientists interested in the social and economic history of ancient China. The data can be used for further insights/analyses on the evolutionary pattern of geo-social architecture, and the geo-history from the viewpoint of social network.